Dividend Policy Determinants: Study in Manufacturing Companies Listed on the Indonesia Stock Exchange - Silaban, Adanan; Nathanael, Adriel Yakobus (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
Dividend policy is a policy that gives a signal to investors to invest in shares in a company. Therefore, research on the determinants of dividend policy is an interesting issue to research. This research aims to determine the influence of managerial ownership, institutional ownership and debt policy on dividend policy. The population in this research is food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022, namely 16 observations from 38 companies with an observation period of 3 years so that the data used is 48 data. The sampling technique uses a purposive sampling method, the type of data used is secondary data in the form of company financial reports, this research uses the multiple linear regression analysis method. The research results show that managerial ownership has a positive and significant effect on dividend policy, while institutional ownership has no significant positive effect on dividend policy, and debt policy has a significant negative effect on dividend policy. The results of this research support the results of previous research. For future research, it is recommended to add factors that are thought to influence dividend policy, and add years of research observation.